(untitled) (American Journal of Islam and Society, 2000)
Jacques Jomier states that this book was written at the request of some nonMuslims living and working in the Muslim world, who were daunted by the seemingly "impenetrable" and "closed" nature of the Qur’an - a statement that is rather surprising when one considers that, for several decades now, contact with the Qur’an has made Islam the fastest growing religion in the Western world. Note especially the author’s statement that "Islam is the Qur’an" and that, according to Christian estimates, Islam will be more practiced in Britain than Christianity by the year 2006. A superficial glance at the text gives the reader the impression that this is an objective piece of work, but on closer examination the author’s preconceptions and personal bias become obvious. In the introduction, for example, Jomier describes his colleagues - the non-Muslims living with Muslims, for whom the book is intended - as having "persevered with their project" (p. ix), and that ’’before the present work was written, it was explored and discussed in two or three closed groups and many of the observations it contains were suggested by this experience" (p. x). He also defines their strategy in both a patronizing and an evangelical tone, saying, "We will succeed only if we are prepared to listen to them [Muslims] tactfully, without taking their positions as hard and fast, knowing that there are different tendencies among them that are capable of development" (p. xi) ...